2015
DOI: 10.1080/10615806.2015.1070833
|View full text |Cite
|
Sign up to set email alerts
|

The role of workaholism in the job demands-resources model

Abstract: These findings suggest that workaholism is a function of a suboptimal work environment and predicts unfavorable employee outcomes. We discuss the theoretical and practical implications of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 62 publications
10
116
0
9
Order By: Relevance
“…A company in this sector was selected because exFor reviews, see Halbesleben and Buckley [48], Schaufeli and Enzmann [49], burnout -Bakker et al [50], and absenteeism -Bakker et al [51]. The research that analyzes the relationship between demands and workaholism has shown that specifically overwork, cognitive and emotional demands, and social stressors are positively related to workaholism [52]. Johnstone and Johnston [24] have shown that those who experience greater work pressure have also higher level of drive to work.…”
Section: Materials and Methods Participants And Proceduresmentioning
confidence: 99%
“…A company in this sector was selected because exFor reviews, see Halbesleben and Buckley [48], Schaufeli and Enzmann [49], burnout -Bakker et al [50], and absenteeism -Bakker et al [51]. The research that analyzes the relationship between demands and workaholism has shown that specifically overwork, cognitive and emotional demands, and social stressors are positively related to workaholism [52]. Johnstone and Johnston [24] have shown that those who experience greater work pressure have also higher level of drive to work.…”
Section: Materials and Methods Participants And Proceduresmentioning
confidence: 99%
“…These changes have contributed to making workers less able to reach a satisfying work-life balance. The issues of WFC and WFE are the central constructs in this area of studies: to simplifying, several studies show that WFC is related to lower work satisfaction, higher turnover intentions, emotional exhaustion and a health impairment process (Colombo and Ghislieri, 2010; Cortese et al, 2010; Molino et al, 2016a; Ghislieri et al, 2017) while WFE is associated to high professional commitment and lower turnover intentions (Russo and Buonocore, 2012; Tummers and Den Dulk, 2013; Ghislieri et al, 2017). These findings indicate that research on WFC and WFE, intertwined with the study of the use of new technologies, can be considered an in-depth exploration of the technostress topics cited above (Ayyagari et al, 2011; Tarafdar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Workload is a job demand that represents the amount of tasks and activities that workers have to carry out (Schaufeli and Taris, 2014). To date, several studies have investigated this (Bakker and Demerouti, 2007; Giunchi et al, 2016; Molino et al, 2016a) and showed that it is one of the main determinants of WFC (Cortese et al, 2010; Ghislieri et al, 2012). The second job demand considered is emotional dissonance, which refers to a discrepancy between felt and displayed emotions (Zapf et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados desse estudo revelaram um modelo preditor complexo da AT, constituído de variáveis individuais e laborais. Esses resultados indicam importante contribuição para a consolidação de um modelo teórico sobre essa temática e ampliação do conhecimento da ciência psicológica e confirmam os modelos teóricos que indicam ser esse um fenômeno psicossocial (Andreassen, Hetland, & Pallesen, 2012;Carlotto et al, 2014;Molino, Bakker, & Ghislieri, 2015;Quinones & Griffiths, 2015).…”
Section: Resultsunclassified